2009
DOI: 10.1021/jf900483t
|View full text |Cite
|
Sign up to set email alerts
|

Native Lignin Structure of Miscanthus x giganteus and Its Changes during Acetic and Formic Acid Fractionation

Abstract: Milled wood lignin (MWL) and acetic and formic acid lignin (AL and FL) from Miscanthus x giganteus bark were produced, respectively, before and after organosolv fractionations under optimal conditions, in terms of organic and hydrochloric acid concentrations, liquid/wood ratio, and reaction time. In order to study the M. x giganteus native lignin structure and its modifications during the fractionation process, the lignins were studied by two-dimensional heteronuclear single quantum coherence (2D-(HSQC)), (13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 26 publications
12
143
1
1
Order By: Relevance
“…The same12 % value was also obtained for γ-acylated cinnamyl alcohol endgroups (I') by integration of their signals. This is a rather low value when compared to those obtained in other plants such as sisal, elephant grass, or Miscanthus that presented, respectively, 68, 39-55, and 46 % of acylation [22,33,34]. Lignin acylation in cardoon stalks occurred exclusively at the Cγ position, as also reported for other plants [35].…”
Section: Lignin Structural Units and Interunit Linkages As Seen By 2dsupporting
confidence: 41%
“…The same12 % value was also obtained for γ-acylated cinnamyl alcohol endgroups (I') by integration of their signals. This is a rather low value when compared to those obtained in other plants such as sisal, elephant grass, or Miscanthus that presented, respectively, 68, 39-55, and 46 % of acylation [22,33,34]. Lignin acylation in cardoon stalks occurred exclusively at the Cγ position, as also reported for other plants [35].…”
Section: Lignin Structural Units and Interunit Linkages As Seen By 2dsupporting
confidence: 41%
“…Furthermore, M. x giganteus showed a low S/G ratio (0.7) and a predominance of -O-4' linkages (up to 93% of all linkages) [17]. Also contains a very low proportion of condensed linkages such as spirodienone ( -1') (detected in a quantity lower than 0.5%), phenylcoumaran ( -5') and resinol ( -') [17]. It is believed that the high acylation at C could be the reason for the low abundance of the double tetrahydrofuran ring from resinol, which requires free hydroxyls in C to be formed [19].…”
Section: Native Lignin Of Miscanthus X Giganteusmentioning
confidence: 95%
“…This is remarkable since several earlier studies showed that acylation at thecarbon commonly occurs in C3-and CAM-grasses [19], whereas M. x giganteus is a C4 grass. Furthermore, M. x giganteus showed a low S/G ratio (0.7) and a predominance of -O-4' linkages (up to 93% of all linkages) [17]. Also contains a very low proportion of condensed linkages such as spirodienone ( -1') (detected in a quantity lower than 0.5%), phenylcoumaran ( -5') and resinol ( -') [17].…”
Section: Native Lignin Of Miscanthus X Giganteusmentioning
confidence: 99%
See 2 more Smart Citations